Determining Purpose of Academic Discipline "Physical Education" for Future Teachers - Ж. О. Цимбалюк; Т. І. Гогіна (OVS LLC, 2016)
The research objective is to determine the purpose of physical education in pedagogical higher educational institutions. Materials and methods. The research used: theoretical analysis and collation of scientific literature; study of guidelines and documents regulating the process of organizing and conducting the discipline "Physical Education" in a higher educational institution; questionnaires. The participants of the experiment were 60 first-year students (enrolled in 2015-2016) of the School of Ukrainian Language and Literature of H. S. Skovoroda Kharkiv National Pedagogical University. Research results. The analysis of the questionnaires revealed low rates of motivational variants in the choice of the sports section related to the future profession. The research specified the purpose of the discipline "Physical Education" in a pedagogical higher educational institution, and defined the health-preserving competence. Conclusions. The specific nature of the pedagogical profession requires that future teachers acquire the health-preserving competence within the discipline "Physical Education", namely, the ability to maintain a general level of physical health needed to conduct social and professional activity.